1995
DOI: 10.1007/bf00328901
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio and sexual dimorphism in the dioecious Borderea pyrenaica (Dioscoreaceae)

Abstract: Sex ratio and sexual dimorphism of Borderea pyrenaica, a long-lived dioecious geophyte endemic to the Pyrenees (north-east Iberian Peninsula), were examined in three alpine populations. In this species, age can be estimated and the sex of nonreproductive adult plants identified. Male plants attain sexual maturity earlier, flower more frequently and grow faster than female plants, whereas females allocate a higher biomass to reproduction than males. These results support the hypothesis that female plants incur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 56 publications
2
54
0
1
Order By: Relevance
“…Females have been reported to have larger reproductive size thresholds in a number of non-protandrous plant (Bawa et al 1982, Lovett Doust & Lovett Doust 1988 and animal (Ayre 1984, Gillanders et al 1999) species, and these differences are frequently attributed to a greater investment in sexual reproduction by females (Darwin 1877, Garcia & Antor 1995, reviewed in Lloyd & Webb 1977. I did not, however, find evidence for differences between females and males in sexual reproductive investment in Ophiactis savignyi: females tended to have a greater mass invested in gonads at any given size relative to males, but this difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Females have been reported to have larger reproductive size thresholds in a number of non-protandrous plant (Bawa et al 1982, Lovett Doust & Lovett Doust 1988 and animal (Ayre 1984, Gillanders et al 1999) species, and these differences are frequently attributed to a greater investment in sexual reproduction by females (Darwin 1877, Garcia & Antor 1995, reviewed in Lloyd & Webb 1977. I did not, however, find evidence for differences between females and males in sexual reproductive investment in Ophiactis savignyi: females tended to have a greater mass invested in gonads at any given size relative to males, but this difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…García-Fayos (2006), because female plants store the most resources in the form of leaves and invest a small proportion of them to increase the immediate reproduction. In some biphasic species (with male and female flowers growing in sexually dimorphic branches that are spatially and temporally isolated), the storage organs of the females are larger than the males; for example, the female phase of Gurania (Cucurbitaceae) and Psiguria (Cucurbitaceae) is preceded by an increase in stem diameter (García & Antor, 1995). In this regard, the hypothesis of the advantage of size predicts that smaller individuals will express the gender that represent lower costs, in this case, male plants, whose expenditure for the production of pollen is lower than the total expenditure of metabolic energy and mineral nutrients for the production of eggs, seeds and fruits (Lovett-Doust & Lovett-Doust, 1988).…”
Section: Resultados Y Discusiónmentioning
confidence: 99%
“…In this regard, the hypothesis of the advantage of size predicts that smaller individuals will express the gender that represent lower costs, in this case, male plants, whose expenditure for the production of pollen is lower than the total expenditure of metabolic energy and mineral nutrients for the production of eggs, seeds and fruits (Lovett-Doust & Lovett-Doust, 1988). The stem of epigaeous cycads retains a covering of dan en ramas sexualmente dimórficas y que están espacial y temporalmente aisladas), los órganos de almacenamiento de las hembras son más grandes que los de los machos; por ejemplo, la fase femenina de Gurania (Cucurbitaceae) y Psiguria (Cucurbitaceae) es precedida por un incremento en el diámetro del tallo (García & Antor, 1995). Al respecto, la hipótesis de la ventaja del tamaño predice que los individuos pequeños expresarán el género que represente menores costos; en este caso, los machos cuyo gasto para la producción de polen es menor que el gasto total de energía metabóli-ca y nutrientes minerales para la producción de los óvulos, semillas y frutos (Lovett-Doust & Lovett-Doust, 1988).…”
Section: Resultados Y Discusiónunclassified
“…For A. tegmentosum in this study, the reproductive components of hermaphrodite trees are also green, but they do not seem to contribute much to growth. García (1995) reported that the total amount of chlorophyll in fruits accounts for almost half the biomass of the aerial part of fruiting female plants, suggesting that photosynthetic activity of green fruits is far less than that of leaves. This phenomenon is likely to vary among species and depend on their reproductive features.…”
Section: Gender-related Allometric Relationshipsmentioning
confidence: 99%